Broiler Performance, Carcass Characteristics, Haematology and Serum Biochemical Parameters as Affected by Hot Red Pepper (Capsicum frutescens) Powder Supplementation - Shawle, Kassa; Urge, Mengistu; Animut, Getachew; Zeryehun, Tesfaheywet (Indian Journal of Animal Nutrition, 2018)
This study was undertaken to evaluate the effects of hot red pepper (Capsicum frutescens) as feed additive on performance and health parameters of broilers. A total of 192 Cobb-500 day-old broiler chicks were randomly distributed into four treatments with three replicates. Hot red pepper (Hrp) was included in the rationat 0 (0Hrp), 0.75 (0.75Hrp), 1.5 (1.5Hrp) and 2.25% (2.25Hrp) in treatment T1, T2, T3 and T4, respectively. Growth performance, carcass characteristics, hematology and serum biochemical parameters were observed. Averagedaily weight gain, feed intake and feed conversion ratio were similar in all the treatments. The birds of T3 group had higher (P